Refresco instantáneo con pulpa microencapsulada a partir de Euterpe oleracea (huasai) y Myrciaria dubia (camu camu) con alto valor nutricional y capacidad antioxidante - Del Aguila Trigoso, Freszia (2024)
The purpose of the work was to obtain the technological parameters for the production of an instant soft drink from Euterpe oleracea (huasaí) and Myrciaria dubia (camu camu), with nutritional value and antioxidant capacity; with a completely experimental design for both the drying and formulation process of the instant soft drink. The results obtained in the atomization process were; 160 °C temperature at 6% gum arabic concentration, using a feed flow rate of 16.5mL/min, for the two pulps Euterpe oleracea and Myrciaria dubia; obtaining a yield of 62.18% for huasaí and 59.20% for camu camu. Corresponding to the sensory analysis, no significant difference in acceptance was found between the two formulations of the instant soft drink. The physicochemical results of formulation A of the instant soft drink containing (huasaí 10g, camu camu 2g, chancaca 14), showed that it has fatty acids 8.62%, energy 422.18 Kcal, total fiber 6.02%, minerals such as; calcium 49mg, magnesium 28mg, phosphorus 15mg and the presence of Vitamin A (betacarotene) 3116mg and (retinol) 4517mg, vitamin C 968.21mg, for formulation B, containing (huasaí 14g, camu camu 2g, chancaca 10g), showed fatty acids 11.61%, energy 436.09 Kcal, total fiber 4.89%, minerals such as calcium 20.48mg, magnesium 12mg, phosphorus 3.90mg, potassium 3.05mg and the presence of vitamin A (beta-carotene) 9347mg and retinol 1668mg and vitamin C 1051.88 mg. Likewise, the microbiological analyzes indicate that the product is harmless since it contains microorganisms within the permitted limits. In addition, the presence of phenolic compounds was found in the two samples, having a free radical and antioxidant capture activity that demonstrates in such a way that the product is bioactive; Therefore, soft drink can be considered a functional food.